Acute neonatal volvulus with congenital enteric duplication, presenting with "currant jelly" stool - William F. Liu; Evans P. Valerie; Heidi H. Lewis; Orestes Borrego (Elsevier, 2020)
We present a clinicopathologic review of a 36-week gestation neonate who acutely presents with currant jelly stool, abdominal tenderness without distension, and dark-colored emesis, found to have an enteric duplication cyst with secondary jejunal volvulus and associated bowel wall ischemia and necrosis. Enteric duplication cysts may occur at all levels of the gastrointestinal tract, and may manifest a range of clinical presentations. Acute presentation with currant jelly stool, usually described with intussusception, has not been previously reported with neonatal volvulus.